Analysis of the shape of x-ray diffraction peaks originating from the hexatic phase of liquid crystal films. (13th April 2017) - Zaluzhnyy, I. A.; Kurta, R. P.; Menushenkov, A. P.; Ostrovskii, B. I.; Vartanyants, I. A.
ABSTRACT: X-ray diffraction studies of the bond-orientational order in the hexatic-B phase of 75OBC and 3(10)OBC compounds are presented. The temperature evolution of an angular profile of a single diffraction peak is analyzed. Close to the hexatic-B–smectic-A transition these profiles can be approximated by the Gaussian function. At lower temperatures in the hexatic-B phase the profiles are better fitted by the Voigt function. Theoretical analysis of the width of diffraction peaks in three-dimentional (3D) hexatics is performed on the basis of the effective Hamiltonian introduced by Aharony and Kardar[1] . Theoretical estimations are in good agreement with the results of x-ray experiments.